Faktor Belanja Modal dan Ukuran Pemerintah Sebagai Prediktor dari Anggaran Pemerintah Daerah di Indonesia - Eka Rosalina; Rini Frima; Yolla Maysanti (Politeknik Caltex Riau, 2022)
This study aims to determine how capital expenditure factors and government size can affect the realization of the 2018-2020 government budget. This study uses a saturated sample, which is a sample consisting of the entire population, namely all provinces in Indonesia for the 2018-2020 period with a total of 34 provinces obtained from the official website of the local government of each province and also from the BPK website, namely https://www.bpk.go .id/ihps. The number of samples used in this study were 102 samples. The data analysis method in this study is the multiple linear analysis method of panel data. In this study, the data were analyzed using STATA 16 software. Based on the test results, the research results obtained that capital expenditure variables and the size of local government negatively affected the level of local government budget realization.